Development Of Novel Protective Strategies For Riga-Fede Disease In Infants A Clinical Trial - Dubey, Alok (Journal of Neonatal Surgery, 2025)
Riga-Fede disease (RFD) is a rare traumatic ulcerative condition observed in infants, typically caused by repetitive friction of the tongue or oral mucosa against natal or neonatal teeth. The present study aims to develop novel protective strategies to prevent and manage RFD through clinical intervention. A prospective clinical trial was conducted on infants diagnosed with RFD to evaluate the efficacy of customized protective oral appliances, bioadhesive gels, and modified feeding techniques in minimizing trauma and promoting ulcer healing. The study included infants aged 3 to 12 months with confirmed RFD. The primary outcomes assessed were reduction in ulcer size, pain relief, and overall healing time. Results indicated that the application of bioadhesive gels combined with a protective oral appliance significantly reduced ulcer progression and improved healing outcomes compared to conventional treatment. The findings highlight the potential of these novel strategies in enhancing the management of RFD and preventing recurrence. Future research should focus on long-term follow-up and further refinement of these protective measures to optimize patient outcomes.